Management of the International Arabic Debate Program at Qatar Debate Center - Agung Muttaqien; Mochammad Deddy Soe'aiddy; Fikni Mutiara Rachma; Muhammad Agus Mulyana (Al-Muyassar: Journal of Arabic Education, 2026)
This research aims to understand the planning, organization, implementation, and monitoring processes of the International Arabic Debate Championship program at QatarDebate, a member of Qatar Foundation. This qualitative research employs a descriptive approach, utilizing interviews, observations, and document analysis to collect data. Data analysis involves reducing, presenting, summarizing, and verifying the data. The research findings are: 1) Planning involves setting the fundamental objectives that promote the art of debate at the global level, understanding the current situation, determining effective participation, establishing criteria for achieving the objectives, and fostering collaboration, including with Qatar Airways and the Algerian international media partner. 2) Organization involves defining activities, such as conducting the debate training course and the International Arabic Debating Championship, assigning responsibilities to staff, volunteers, and certified trainers, setting dates, and providing necessary resources. Implementation includes classifying the participating country's team based on native and non-native speakers, encouraging participants in the championship rounds, fostering respect in the exchange of ideas, and overseeing the judging process. Monitoring involves internal evaluation after the program's conclusion, analyzing the competition's processes for strengths and weaknesses, and revising the International Arabic Debating Program to address future challenges. The management model used, based on the POAC theory, encompasses planning and preparing the training, organizing the championship process, ensuring optimal debate participation, monitoring the championship, and assessing the learning experience for debaters, participants, and learners.